2014
DOI: 10.1093/ndt/gfu125
|View full text |Cite
|
Sign up to set email alerts
|

New Dialysis Techniques

Abstract: Introduction and Aims: The Frequent Hemodialysis Network Nocturnal trial randomized 87 subjects to 6 times per week home nocturnal hemodialysis (FNHD) or to 3 times per week hemodialysis (3HD) for 1 year. Subjects were subsequently free to modify their treatment schedule. We describe effects of randomized treatment assignment on mortality over a median follow-up of 3.7 years. Methods: We obtained dates of death and kidney transplantation through July 2011 using linkage to USRDS and queries of study centers. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…With the development of more efficient dialyzers in the 1980s and the increased focus on reduction of urea, a small, readily dialyzable solute, as the indicator of dialysis adequacy, the typical dialysis session length decreased from 6-8 to 2.5-4 hours (28). More recently, several large observational studies have found an association between longer dialysis session duration and lower mortality risk (29)(30)(31); however, reduced mortality with longer dialysis time is not evident in all such analyses (32), and an effect of dialysis time on mortality has not yet been established in a sufficiently powered randomized trial. Increased dialysis time may have contributed to the benefit of daily dialysis on the important surrogate outcome, left ventricular mass index (LVMI): in the Frequent Hemodialysis Network (FHN) Trial, the total weekly time was greater with dialysis 6 times/ wk than with 3 times/wk, but the relative contributions of increased solute clearance and lower ultrafiltration rate resulting from increased dialysis time is not known (25).…”
Section: The Importance Of Time For Solute Clearancementioning
confidence: 99%
“…With the development of more efficient dialyzers in the 1980s and the increased focus on reduction of urea, a small, readily dialyzable solute, as the indicator of dialysis adequacy, the typical dialysis session length decreased from 6-8 to 2.5-4 hours (28). More recently, several large observational studies have found an association between longer dialysis session duration and lower mortality risk (29)(30)(31); however, reduced mortality with longer dialysis time is not evident in all such analyses (32), and an effect of dialysis time on mortality has not yet been established in a sufficiently powered randomized trial. Increased dialysis time may have contributed to the benefit of daily dialysis on the important surrogate outcome, left ventricular mass index (LVMI): in the Frequent Hemodialysis Network (FHN) Trial, the total weekly time was greater with dialysis 6 times/ wk than with 3 times/wk, but the relative contributions of increased solute clearance and lower ultrafiltration rate resulting from increased dialysis time is not known (25).…”
Section: The Importance Of Time For Solute Clearancementioning
confidence: 99%